2020
DOI: 10.1124/pharmrev.120.000011
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in G Protein–Coupled Receptors: Mechanisms, Pathophysiology and Potential Therapeutic Approaches

Abstract: There are approximately 800 annotated G protein-coupled receptor (GPCR) genes, making these membrane receptors members of the most abundant gene family in the human genome. Besides being involved in manifold physiologic functions and serving as important pharmacotherapeutic targets, mutations in 55 GPCR genes cause about 66 inherited monogenic diseases in humans. Alterations of nine GPCR genes are causatively involved in inherited digenic diseases. In addition to classic gain-and loss-of-function variants, oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
74
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 451 publications
(386 reference statements)
0
74
0
Order By: Relevance
“…The allele frequency spectrum represents both low-frequent variants such as singletons only found in single samples and variants with higher frequency such as I158V 13 found in 1 in 492 individuals (mean AF across cohorts: 0.27%). Furthermore, the GLP-1 variant K117N 26 and the glucagon variant R70H Glucagon,18 are among the most frequent, respectively occurring 1 in 33,282 and 1 in 23,951 individuals.…”
Section: Glucagon Glp-1 and Glp-2 Are More Conserved And More Likely To Be Functionally Impacted By Genetic Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…The allele frequency spectrum represents both low-frequent variants such as singletons only found in single samples and variants with higher frequency such as I158V 13 found in 1 in 492 individuals (mean AF across cohorts: 0.27%). Furthermore, the GLP-1 variant K117N 26 and the glucagon variant R70H Glucagon,18 are among the most frequent, respectively occurring 1 in 33,282 and 1 in 23,951 individuals.…”
Section: Glucagon Glp-1 and Glp-2 Are More Conserved And More Likely To Be Functionally Impacted By Genetic Variationmentioning
confidence: 99%
“…GPCRs mediate the therapeutic effect of approximately 34% of drugs on the market (24). Recent studies have shown extensive variability in GPCRs, and mutations within the coding region can lead to several monogenic diseases or to altered drug responses (25,26). Therefore, missense variants in GCG, coding for the hormones may play a role in metabolic diseases or affect the treatment of these.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of the residues involved in allosteric communication will also allow us to engineer GPCR mutants that would bias the receptor toward one signaling pathway over the other. In the same vein, many disease‐associated mutations are located in GPCRs [7,8] and these mutations can lead to gain or loss of function of the receptors. Identifying the residues involved in allosteric communication and their overlap with disease‐associated mutations would allow us to annotate the functional role of these mutations at a protein level and open up therapeutic opportunities.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the GPCRs localized in the nuclear membrane may also be influenced by these phenomena and be involved in the pathophysiology and development of non-communicable diseases [ 60 , 61 ]. Moreover, scientific data also indicate the occurrence of constitutively active mutations in GPCRs that have been associated with diseases [ 62 , 63 ], which can also have a role in the pathophysiological processes.…”
Section: Nuclear Gpcrs In Non-communicable Diseasesmentioning
confidence: 99%